LEGAL PRINCIPLES OF ECONOMIC POLICY IN THE ISLAMIC REPUBLIC OF IRAN - Gandmani, Ayoub Ahmadi; Sadeghi, Mohammad; Baseri, Babak (Gênero & Direito, 2019)
In this research, we first describe and explain the terminology and key words used in the title of the research, namely "Legal Basics", "Economic Policy" and "Islamic Republic of Iran". After explaining the terms and key words used in the research title, this question has been raised, what is the legal basis of economic policy in the Islamic Republic of Iran? Given the clarification of the concept of legal principles and other words used in the research title, the answer to this question is in the highest and most valid legal document in the country, the constitution. Our assumption is that the legal basis for economic policy in the Islamic Republic of Iran is Islamic economics, in other words, the main constitutional basis for economic policy, the Islamic economy, in other words, what is the right of the people and the duty of the state is to make policy according to constitutional criteria. Finally, in view of the goals and ideals of the Islamic Revolution of Iran and the post-revolutionary atmosphere of the Islamic Republic, and the Islamic attitudes of the main legislators, which have contributed to the introduction of the constitution and the various principles of the constitution, and ultimately the principles of the constitution in which the use of Islamic economics has been used, has been answered to the question in a descriptive-analytical method